القرار الجراحي في انسدادات الأمعاء التالية للجراحة البطنية (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة 50 مريضاً دخلوا مشفى الأسد الجامعي في اللاذقية خلال الفترة الواقعة بين عامي 2004-2002  في قسم الجراحة بتشخيص مبدئي انسداد أمعاء (حاد أو تحت حاد) مع سوابق فتح بطن جراحي. تميزت الدراسة بسيطرة الذكور بنسبة 70% خاصة في العقدين الخامس والسادس. كما تضمنت دراسة الأعراض والعلامات السريرية حيث كان الألم البطني هو العرض المسيطر بنسبة  96%, وتحديد نمط وتصنيف وموقع الانسداد بالاعتماد على القصة المرضية والفحص السريري والاستقصاءات الشعاعية والفحوص المتممة: أ ـ نمط الانسداد: آلي (ميكانيكي) 96%. ب ـ تصنيف الانسداد: انسداد تام 78%. ج ـ موقع الانسداد: انسداد علوي 70%. تم توزيع المرضى إلى مجموعتين علاجيتين (جراحي ـ محافظ) وفقاً واعتماداً على معايير سريرية وشعاعية ومخبرية حيث كانت نسبة العلاج المحافظ 44%, ونسبة العلاج الجراحي 56%.   The research included 50 patients in AL-ASSAD academic hospital in Lattakia: (2002-2004). The research was carried on patients whom were admitted to the department of surgery with initial diagnoses of intestinal obstruction (acuteـsub acute) with previous laparatomy. The research was characterized by a high rate of male patients 70%, especially those in their 5th and the 6th decades. The research comprised the following: Studying clinical signs and symptoms in which the abdominal pain was the prevailing   symptom 96%. Depending on the history, clinical examination, radiography investigation and comlementary examination we recognized: • Obstruction type: Mechanical obstruction  96%.• Obstruction classification: Complete obstruction 78%.• Obstruction location: Upper obstruction 70%.   Depending on clinical, radiography and serology criteria the patients were divided into two therapeutic groups (conservative ـ surgical) in which the conservative rate was 44%, and the surgical was 56%.